2018
DOI: 10.1038/s41598-017-19135-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Distal Mutations on the Structure, Dynamics and Catalysis of Human Monoacylglycerol Lipase

Abstract: An understanding of how conformational dynamics modulates function and catalysis of human monoacylglycerol lipase (hMGL), an important pharmaceutical target, can facilitate the development of novel ligands with potential therapeutic value. Here, we report the discovery and characterization of an allosteric, regulatory hMGL site comprised of residues Trp-289 and Leu-232 that reside over 18 Å away from the catalytic triad. These residues were identified as critical mediators of long-range communication and as im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 51 publications
(56 reference statements)
1
36
0
Order By: Relevance
“…That said, a design rule to emerge from this study is that certain charged side chains near the termini of helices stabilise the constructs, which is in agreement with conclusions drawn from a previous study combining bioinformatics and rational design of single a helices [85]. [86]. Therefore, design strategies that incorporate, or at least consider, the functional aspect at an early stage could ultimately lead to more successful outcomes.…”
Section: Fragment-based Computational Design Beyond Protein Engineeringsupporting
confidence: 86%
“…That said, a design rule to emerge from this study is that certain charged side chains near the termini of helices stabilise the constructs, which is in agreement with conclusions drawn from a previous study combining bioinformatics and rational design of single a helices [85]. [86]. Therefore, design strategies that incorporate, or at least consider, the functional aspect at an early stage could ultimately lead to more successful outcomes.…”
Section: Fragment-based Computational Design Beyond Protein Engineeringsupporting
confidence: 86%
“…The raw data at a given wavelength, λ (nm) were converted into concentration-independent parameter [θ] λ (deg cm is the mean residue weight of the protein, l is the path length of the cell in centimeters, and c is the protein concentration in mg ml −1 ). Baseline was corrected and smoothed (within permissible limits) by using the inbuilt CDNN software (Applied Photo physics, Surrey, UK) of the unit [16][17][18]. .…”
Section: Circular Dichroism Spectroscopy Analysismentioning
confidence: 99%
“…Circular Dichroism were performed for structural conformation and functional responses of a protein. Tyukhtenko et al, 2018 showed that CD spectra is indicative of the secondary structure prediction and no conformational change or folding may occurs which might be possible due to nonconservative substitutions at certain at certain length of spectra. Anwer et al, 2016 reported that secondary structural changes of a protein can be assessed from CD spectra and the protein follow two state folding mechanism.…”
Section: Circular Dichroism Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular details of allosteric communications between the active site and the distal regions are still poorly understood. We have shown previously that the native state of hMGL is a conformational ensemble and that introducing an allosteric perturbation by single mutation of a critical distal residue can significantly affect the networks of allosteric interactions, resulting in conformational rearrangements in the active site and other regions of hMGL 37 .…”
Section: Introductionmentioning
confidence: 99%